Tabernacle and temple a brief outline of the Scriptural accounts and spiritual significance of the Tabernacle, Levitical offerings, priesthood and festivals, and of the temple - Tatford, Frederick Albert, 1901- (Kilmarnock, Scotland John Ritchie)
Includes bibliographical references.
Brethren writer.
Keywords: Bible. O.T. Exodus -- criticism, interpretation, etc; Tabernacle -- typology